VISUALIZING THE PERFORMANCE OF INFORMATION PROCESSING TOOLS IN THE EDUCATIONAL PROCESS, MULTIMEDIA EDUCATIONAL ENVIRONMENT - Erkayev Xusan Axmadaliyevich; Ibrohimova Iqbolxon Mirsadil Qizi (Scholar Express Journal, 2022)
The science that is taught in this scientific article is rich in the methods of explaining the processes of subjects to the students by visualizing them in the multimedia educational environment.
Keywords: Education; multimedia; audio; information